A Genetic Screen Identifies Interferon-α Effector Genes Required to Suppress Hepatitis C Virus Replication - Fusco, Dahlene N. (2013)
BACKGROUND & AIMS: Hepatitis C virus (HCV) infection is a leading cause of end-stage liver disease. Interferon (IFN)-α is an important component of anti-HCV therapy; it upregulates transcription of IFN-stimulated genes (ISGs)—many of which have been investigated for their anti-viral effects. However, all the genes required for the anti-viral function of IFN-α (IFN effector genes, IEGs) are not known. IEGs include not only ISGs, but other non-transcriptionally induced genes that are required for the anti-viral effect of IFN-α. In contrast to candidate approaches based on analyses mRNA expression, identification of IEGs requires a broad functional approach. METHODS: We performed an unbiased genome-wide small-interfering (si)RNA screen to identify IEGs that inhibit HCV. Huh7.5.1 hepatoma cells were transfected with siRNAs, incubated with IFN-α, and then infected with JFH1 HCV. Cells were stained using HCV core antibody, imaged, and analyzed to determine the percent infection. Candidate IEGs detected in the screen were validated and analyzed further. RESULTS: The screen identified 120 previously unreported IEGs. From these, we more fully evaluated 9 (ALG10, BCHE, DPP4, GCKR, GUCY1B3, MYST1, PPP3CB, PDIP1, SLC27A2) and demonstrated that they enabled IFN-α–mediated suppression of HCV at multiple steps of its lifecycle. Expression of these genes had more potent effects against flaviviridae, because a subset were required for IFN-α to suppress dengue virus but not influenza A virus. Furthermore, many of the host genes detected in this screen (92%) were not transcriptionally stimulated by IFN-α; these genes represent a heretofore unknown class of non-ISG IEGs. CONCLUSION: We performed a whole-genome loss-of-function screen to identify genes that mediate the effects of IFN-α against human pathogenic viruses. We found that IFN-α restricts HCV via actions of general and specific IEGs.